PELATIHAN DASAR AKUNTANSI PEMILIK UMKM DI KABUPATEN BANGKA TENGAH - Sumiyati, Sumiyati; Fahria, Izma; Khairiyansyah, Khairiyansyah; Aprilian, Rahil (Institut Agama Islam Negeri Ternate, 2023)
MSME owners in Central Bangka also have not been able to prepare financial reports in accordance with applicable financial standards. This is because MSME owners do not know the basics of accounting records. Even though there are quite a lot of Android-based accounting and financial reporting applications available with various choices according to the needs of the owner. This service uses the lecture method to introduce the basics of accounting and demonstration methods for assisting in the preparation of Android-based financial reports. This activity is expected to provide knowledge for PPKL and MSME owners regarding the basics of accounting and at the same time prepare financial reports for MSME owners. Evaluation of this activity is carried out by providing feedback sheets in the form of pre-test and post-test to measure the level of understanding of participants.